DEVELOPING LEADERSHIP COMMUNICATION STYLES: A SURVEY RESEARCH OF TM POINT - Abd Manaf, Norhayati; Md Ismail, Zarina; Hassim, Nurzihan (Journal of Human Capital Development (JHCD), 2010)
This research paper will focus on the aspect of leadership and its function in leading and improvising employee effectiveness and performance in the organization. The case study selected is the improvement of fixed line application services at TM Point upon re-branding exercise carried out by Telekom Malaysia Berhad in 2005. A major player in the telecommunication industry, TM Berhad was privatised in 1984 and continued to spread its wings and diversified its business in the communication service. Realizing its rapid expansion and to catch up with uprising competitors in the industry, TM felt the heat to reposition themselves among the public community and hence decided to undergo a massive re-branding exercise. Among the many services offered by TM, this paper shall look particularly into the fixed line application services at TM point upon re-branding exercise, particularly on the aspect of the relationship between effective leadership and improvement on employees’ performance. Applying a simple qualitative method, this research will be done by carrying out in-depth interviews with two (2) personnel each from the top management and lower management level of TM Point outlet. This study will also try to determine whether the leadership style applied is similar to the model suggested by Blake & Mouton Managerial Grid leadership model. This paper shall contribute to the further understanding of the leadership communication and its applicability in the competitive corporate world. Keywords: organization communication, leadership communication